Highly effective and reusable sulfonated pentablock copolymer nanocomposites for water purification applications. Issue 72 (25th September 2017) - Filice, S.; D'Angelo, D.; Scarangella, A.; Iannazzo, D.; Compagnini, G.; Scalese, S.
Abstract : Sulfonated pentablock copolymer nanocomposites loaded with TiO2 or graphene oxide show their effectiveness in water purification applications. Abstract : Nanocomposite membranes based on the use of a sulfonated pentablock copolymer (s-PBC) were prepared and investigated for the first time for water purification applications. The s-PBC is a thermoplastic elastomer with discrete sequences of ionic (sulfonated) and non-ionic (unsulfonated) blocks. Titania particles and graphene oxide (GO) were dispersed in the polymeric matrix and nanocomposite membranes (named s-PBC–TiO2 and s-PBC–GO, respectively) were prepared by drop casting. The chemical, structural and morphological properties of the nanocomposite membranes were characterized by scanning electron microscopy (SEM), Raman spectroscopy, X-ray diffraction (XRD) and thermogravimetric analysis (TGA). The adsorption properties and the photocatalytic activity of such nanocomposite membranes were investigated by analysing the removal of dyes from water solutions and the degradation of methylene blue (MB) and methyl orange (MO) under UV-visible light irradiation. The role played by the direct interaction of the polymer with the contaminant is also considered. Both the s-PBC–GO and s-PBC–TiO2 nanocomposites show high efficiency in dyes adsorption and photocatalytic degradation. All the nanocomposites investigated in the present study are able to degrade more than the 90% of the initial MB concentration either in dark or under irradiation. The introduction of the fillers in s-PBC favors a fast formation of MB aggregates. MO dye removal from water is efficiently achieved by s-PBC–GO and s-PBC–TiO2 . In particular, s-PBC–GO is a safer material to be used for MO removal with respect to s-PBC–TiO2, since in the first case no formation of aromatic intermediate compounds is observed under UV-visible light irradiation.